Comparing the Effects of Two Culture Methods to Determine the Total Heterotrophic Bacterial Colony Count in Hospital Purified Water - Xiongjing Cao; Huangguo Xiong; Yunzhou Fan; Lijuan Xiong (Springer, 2024)
Abstract Background Accurately detecting the quantity of microorganisms in hospital purified water is of significant importance for early identification of microbial contamination and reducing the occurrence of water-borne hospital infections. The choice of detection method is a prerequisite for ensuring accurate results. Traditional Plate Count Agar (PCA) belongs to a high-nutrient medium, and there may be limitations in terms of accuracy or sensitivity in detecting microorganisms in hospital purified water. On the other hand, Reasoner's 2A agar (R2A) has characteristics, such as low-nutrient levels, low cultivation temperature, and extended incubation time, providing advantages in promoting the growth of aquatic microorganisms. This study, through comparing the differences in total colony counts between two detection methods, aims to select the method more suitable for the growth of aquatic microorganisms, offering new practical insights for accurately detecting the total count of heterotrophic bacteria in hospital purified water. Methods The most commonly used plate count agar (PCA) method, and the R2A agar culture were adopted to detect microorganisms and determine the total number of bacterial colonies in the water for oral diagnosis and treatment water and terminal rinse water for endoscopes in medical institutions. The two water samples were inoculated by pour plate and membrane filtration methods, respectively. Using statistical methods including Spearman and Pearson correlation, Wilcoxon signed-rank sum test, paired-Chi-square test, and linear regression, we analyze the differences and associations in the bacterial counts cultivated through two different methods. Results In 142 specimens of the water, the median and interquartile range of the heterotrophic bacterial colony number under the R2A culture method and under the PCA culture method were 200 (Q1-Q3: 25-18,000) and 6 (Q1-Q3: 0-3700). The total number of heterotrophic bacteria colonies cultured in R2A medium for 7 days was more than that cultured in PCA medium for 2 days (P < 0.05). The linear regression results showed a relatively strong linear correlation between the number of colonies cultured by the R2A method and that cultured by the PCA method (R 2 = 0.7264). The number of bacterial species detected on R2A agar medium is greater than that on PCA agar medium. Conclusion The R2A culture method can better reflect the actual number of heterotrophic bacterial colonies in hospital purified water. After logarithmic transformation, the number of colonies cultured by the two methods showed a linear correlation.